Study on Fused Filament Fabrication (FFF) 3D Printer Parameter for Polyproplene Biomedical 3D Printing - Aulolazmi, Nurul Nadhirah; Kamarudin , Khairu; Radin Khairul Faizi (Progress in Engineering Application and Technology, 2025)
The increasing demand for high-quality and cost-effective biomedical implants has led to exploration of advanced manufacturing technologies, including fused filament fabrication. This study focuses on optimizing FFF parameters for polypropylene (PP), a material valued for its chemical resistance, low density, and flexibility. Challenges such as warping and poor adhesion require precise parameter optimization to ensure high-quality prints. A full factorial design of experiments was conducted using Minitab software, with infill density (ID) of 50% and 100% and layer height (LH) of 0.1mm and 0.15mm on tensile, charpy impact, and flexural strengths. Mechanical testing was conducted on samples printed using an Ultimaker 2+ 3D printer, adhering to ASTM standards. Analysis of Variance (ANOVA) was conducted to identify the significant effects of the parameters and their interactions. The results showed that optimized settings of 0.15mm layer height and 70.7071% infill density yielded superior tensile and impact strength, demonstrating the significance of parameter selection in achieving enhanced mechanical performance. This study contributes valuable insights into 3D printing parameters for polypropylene in biomedical applications. By addressing key challenges in achieving mechanical integrity, this research lays the groundwork for further advancements in the production of high-quality, patient-specific biomedical implants.